Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(\frac{x-3}{x+5}=\frac{5}{7}\)
\(\Rightarrow\left(x-3\right).7=\left(x+5\right).5\)
\(\Rightarrow7x-21=5x+25\)
\(\Rightarrow7x-5x=21+25\)
\(\Rightarrow2x=46\)
\(\Rightarrow x=23\)
Vậy \(x=23\)
b) \(\frac{7}{x-1}=\frac{x+1}{9}\)
\(\Rightarrow\left(x-1\right).\left(x+1\right)=7.9\)
\(\Rightarrow\left(x-1\right)x-\left(x+1\right)=7.9\)
\(\Rightarrow x^2-x-x-1=63\)
\(\Rightarrow x^2-1=63\)
\(\Rightarrow x^2=64\)
\(\Rightarrow x=8\) hoặc \(x=-8\)
Vậy \(x=8\) hoặc \(x=-8\)
c) \(\frac{x+4}{20}=\frac{5}{x+4}\)
\(\Rightarrow\left(x+4\right)^2=100\)
\(\Rightarrow x+4=\pm10\)
+) \(x+4=10\Rightarrow x=6\)
+) \(x+4=-10\Rightarrow x=-16\)
Vậy \(x\in\left\{6;-16\right\}\)
a) \(x-\frac{2}{5}=\frac{5}{7}\)
\(x=\frac{2}{5}+\frac{5}{7}\)
\(x=\frac{14}{35}+\frac{25}{35}=\frac{39}{35}\)
b)
\(\frac{-2}{5}x=\frac{4}{15}\)
\(x=\frac{4}{15}:-\frac{2}{5}\)
\(x=\frac{4}{15}\cdot-\frac{5}{2}=-\frac{2}{3}\)
c) \(2x\left(x-\frac{1}{7}\right)=2x^2-\frac{2x}{7}\)
d) \(\frac{1}{2}+\frac{3}{4}x=\frac{1}{4}\)
\(\frac{3}{4}x=\frac{1}{4}-\frac{1}{2}\)
\(\frac{3}{4}x=-\frac{1}{4}\)
\(x=-\frac{1}{4}\cdot\frac{4}{3}=-\frac{1}{3}\)
f) \(\frac{11}{12}-\left(\frac{2}{5}+x\right)=\frac{2}{5}\)
\(\frac{2}{5}+x=\frac{11}{12}-\frac{2}{5}=\frac{31}{60}\)
\(x=\frac{31}{60}-\frac{2}{5}=\frac{7}{60}\)
Câu a đề thiếu vế phải rồi bạn
b: \(\Leftrightarrow x\cdot0+1=0\)
=>0x+1=0(vô lý)
A = \(\frac{5}{4}.\left(5-\frac{4}{3}\right).\frac{1}{11}\)
A = \(\frac{5}{44}\left(5-\frac{4}{3}\right)\)
A = \(\frac{25}{44}-\frac{5}{33}\)
A = \(\frac{25.3}{4.11.3}-\frac{5.4}{3.11.4}\)
A = \(\frac{75}{132}-\frac{20}{132}\)
A = \(\frac{55}{132}\)
B = \(\frac{3}{4}:\left(-12\right).\left(-\frac{2}{3}\right)\)
B = \(\frac{-1}{16}.\left(-\frac{2}{3}\right)\)
B = \(\frac{1}{24}\)
C = \(\frac{5}{4}:\left(-15\right).\left(-\frac{2}{5}\right)\)
C = \(\frac{-1}{12}.\left(-\frac{2}{5}\right)\)
C = \(\frac{1}{30}\)
D = \(\left(-3\right).\left(\frac{2}{3}-\frac{5}{4}\right):\left(-7\right)\)
D = \(\frac{3}{7}.\left(\frac{8}{12}-\frac{15}{12}\right)\)
D = \(\frac{3}{7}.\left(-\frac{7}{12}\right)\)
D = \(\frac{-3}{12}\)
D = \(\frac{-1}{4}\)